Ethnophysics of Klepon: Exploring Physics Concepts in Traditional Pasuruan Snack - Sari, Irasikah Julia; Syafira, Riska; Zakkiya, Yoda Hilan; Ambarsari, Riana; Saputra, Oka (Mitra Edukasi dan Publikasi, 2024)
Local wisdom plays a crucial role in preserving cultural heritage and embedding scientific knowledge within traditional practices. This study explores the physics concepts inherent in the traditional process of making Klepon, a local snack from Pasuruan, and examines the community's response to this cultural practice. Using a qualitative descriptive research method, the study gathered in-depth data to uncover the underlying physical principles and societal perceptions. The findings reveal that making traditional Klepon involves key physics concepts such as pressure, phase changes, temperature, heat, and Archimedes' principle. Additionally, the research indicates the positive reception of these traditional snacks by the local community and consumers. The study concludes that the preparation of Klepon embodies significant physics concepts and that there is strong community support for the preservation and continued development of this cultural heritage.